Iterative transcription factor screening enables rapid generation of microglia-like cells from human iPSC - Songlei Liu; Li Li; Fan Zhang; Mariana Garcia-Corral; Katharina Meyer; Patrick R. J. Fortuna; Björn van Sambeek; Evan Appleton; Alex H. M. Ng; Parastoo Khoshakhlagh; Yuancheng Ryan Lu; James Cameron; et al. (Nature Communications)
Abstract Differentiation of induced pluripotent stem cells (iPSCs) into specialized cell types is essential for uncovering cell-type specific molecular mechanisms and interrogating cellular function. Transcription factor screens have enabled efficient production of a few cell types; however, engineering cell types that require complex transcription factor combinations remains challenging. Here, we report an iterative, high-throughput single-cell transcription factor screening method that enables the identification of transcription factor combinations for specialized cell differentiation, which we validated by differentiating human microglia-like cells. We found that the expression of six transcription factors, SPI1, CEBPA, FLI1, MEF2C, CEBPB, and IRF8, is sufficient to differentiate human iPSC into cells with transcriptional and functional similarity to primary human microglia within 4 days. Through this screening method, we also describe a novel computational method allowing the exploration of single-cell RNA sequencing data derived from transcription factor perturbation assays to construct causal gene regulatory networks for future cell fate engineering.